2015
DOI: 10.1186/s40623-015-0182-6
|View full text |Cite
|
Sign up to set email alerts
|

A micro-Raman and infrared study of several Hayabusa category 3 (organic) particles

Abstract: Three category 3 (organic) particles (RB-QD04-0001, RB-QD04-0047-02, and RA-QD02-0120) and so-called 'white object' found in the sample container have been examined by micro-Raman and infrared (IR) spectroscopy. In addition, several artificial substances that could occur as possible contaminants and chondritic insoluble organic matter (IOM) prepared from the Murchison CM2 chondrite were analyzed. The Raman spectra of the particles show broad G-band and weak D-band. The G-band parameters plot in the disordered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The Itokawa particles returned by the first Hayabusa mission, for example, were shown to be composed of proteic amino acids at blank levels only (Naraoka et al 2012). Their results were supported by several other preliminary analyses of the Itokawa particles (e.g., Raman spectroscopy, X-ray absorption near edge structure (XANES) spectroscopy) (Kitajima et al 2015;Uesugi et al 2014;Yabuta et al 2014), which suggested that although organic materials were present, it was difficult to ascertain their extraterrestrial origin. Other than identifying amino acids that have rare biological occurrence and determining the relative amino acid abundances and enantiomeric ratio, stable isotope ratio is a reliable and convenient tool used to tell apart terrestrial and extraterrestrial amino acids, as biology preferentially uses lighter isotopes, while amino acids formed by abiotic processes in cold environments are more enriched in heavier isotopes.…”
Section: Introductionsupporting
confidence: 59%
“…The Itokawa particles returned by the first Hayabusa mission, for example, were shown to be composed of proteic amino acids at blank levels only (Naraoka et al 2012). Their results were supported by several other preliminary analyses of the Itokawa particles (e.g., Raman spectroscopy, X-ray absorption near edge structure (XANES) spectroscopy) (Kitajima et al 2015;Uesugi et al 2014;Yabuta et al 2014), which suggested that although organic materials were present, it was difficult to ascertain their extraterrestrial origin. Other than identifying amino acids that have rare biological occurrence and determining the relative amino acid abundances and enantiomeric ratio, stable isotope ratio is a reliable and convenient tool used to tell apart terrestrial and extraterrestrial amino acids, as biology preferentially uses lighter isotopes, while amino acids formed by abiotic processes in cold environments are more enriched in heavier isotopes.…”
Section: Introductionsupporting
confidence: 59%
“…Much has been learned from the study of the organic contamination within and on the surfaces of sample return capsules, such as Hayabusa (e.g., Kitajima et al. ) and Stardust (Sandford et al. ).…”
Section: Curation Considerations and Description Of The Facilitymentioning
confidence: 99%
“…For sample return missions, in particular, any successful analysis of the indigenous material must include an assessment of what possible contaminants might ultimately accumulate on and in the samples during the sequence of steps from sample acquisition through to the final testing in the laboratory. Much has been learned from the study of the organic contamination within and on the surfaces of sample return capsules, such as Hayabusa (e.g., Kitajima et al 2015) and Stardust (Sandford et al 2010). Witness plates, kept close to the samples during various stages, from spacecraft to curation facility, are commonly used to record accumulated contaminants, providing a record of the intrinsic organic content released by the spacecraft's sampling system and associated hardware, and enabling tracking of contaminant introduction and an assessment of cleanliness of the system (e.g., Sandford et al 2010).…”
Section: Curation Considerations and Description Of The Facilitymentioning
confidence: 99%
“…The category 1 and 2 particles (silicate particles) were confirmed to be indigenous to the asteroid, but the category 3 particles, made up of carbonaceous materials, were determined by a sequential analysis to be terrestrial or artefact materials of multiple origins, (e.g. Ito et al 2014;Uesugi et al 2014;Yabuta et al 2014;Kitajima et al 2015;Naraoka et al 2015).…”
Section: Introductionmentioning
confidence: 99%